Prophylactic Administration of Low Dose Midazolam and Ketamine in Prevention of Profound Hypotension in Severely Anxious Females Undergoing Cesarean Section - Majeed, Kaukab; Ali, Chaudhry Amjad; Khan, Fatima Sharif; Hussain, Akhtar; Ansari, Kaswar Sajjad; Qureshi, Sajjad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of a combination of Midazolam and Ketamine in providing anxiolysis to prevent profound hypotension in severely anxious patients undergoing cesarean section.Study Design: Quasi-Experimental StudyPlace and Duration of Study: Combined Military Hospital Quetta, Pakistan from Mar to Apr 2023.Methodology: The study population included female patients of reproductive age group undergoing lower segment cesarean section under spinal anesthesia. A total of 100 patients were recruited. The study sample was divided into two sets. The first set of patients was labeled Group-A and second was labeled as Group-B. Visual Analogue Scale for Anxiety (VAS‐A) was used to assess the anxiety in all patients. Group-A received premedication (Ketamine and Midazolam) and Group-B patients didn’t receive the premedication and they were only given Verbal Reassurance. The primary outcome was frequency of hypotension in patients of moderate-severe anxiety.Results: The frequency of the adverse outcomes was higher in Group-B as compared to Group-A. The frequency of tachycardia was 1(2%) versus 17(34%), hypotension was 1(2%) versus 17(34%), nausea/vomiting was 2(4%) versus 9(18%), shivering was 2(4%) versus 9(18%), and Diaphoresis was 2(4%) versus 5(10%) in Group-A versus Group-B respectively. Conclusion: The combination of low dose Midazolam (0.03mg/kg) and Ketamine (0.2mg/kg) prevents anxiety related hypotension in gravid female undergoing cesarean section under spinal anesthesia.